Adsorpsi Tembaga (Cu (II)) Menggunakan Limbah Cangkang Kepiting - Rida Sari Juli Anti; Drastinawati Drastinawati; Silvia Reni Yenti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Adsorption is one of the most widely used techniques for controlling water pollution. Adsorption kinetics are very important to determine the performance of the adsorbent and get the mechanism that occurs during the adsorption process. The purpose of this study was to determine the effect of metal concentration and adsorption time on crab shell absorption and to test the Cu (II)adsorption kinetics model using pseudo first order (Lagergren) and pseudo second order kinetics (Ho and McKay). Cu (II) solution with varying concentrations of 1,981 mg/l; 4,138 mg/l and6,263 mg/l are adsorbed using crab shells. The solution sample was taken with a time interval of 0, 10, 20, 30, 60, 90, 120 and 150 minutes as much as 10 mL then centrifuged. The centrifugedfiltrate is then analyzed using AAS to measure the remaining Cu (II) concentration. The results showed that the highest of adsorption capacity at the concentration of Cu (II) metal 1,981 mg/lwas 0,737 mg/g in the 30 minute; the concentration of 4,138 mg/l was 1,784 mg/g in the 60 minute and the concentration of 6,263 mg/l was 2,816 mg/g in the 90 minute. The fitted kineticmodel for Cu (II) adsorption using crab shells is pseudo second order model (Ho and McKay) with k2 value is 2,225; 1,432; 1,345 g/mg.min and qe value is 0,737; 1,784; 2,816 mg/g for aconcentration of 1,981; 4,138 and 6,263 mg/l.Keywords : adsorption, crab shells, Cu (II), adsorption capacity, kinetics.